2019
DOI: 10.1096/fj.201900351r
|View full text |Cite
|
Sign up to set email alerts
|

Renal progenitor cells revert LPS‐induced endothelial‐to‐mesenchymal transition by secreting CXCL6, SAA4, and BPIFA2 antiseptic peptides

Abstract: Endothelial dysfunction is a hallmark of LPS‐induced acute kidney injury (AKI). Endothelial cells (ECs) acquired a fibroblast‐like phenotype and contributed to myofibroblast generation through the endothelial‐to‐mesenchymal transition (EndMT) process. Of note, human adult renal stem/progenitor cells (ARPCs) enhance the tubular regenerative mechanism during AKI but little is known about their effects on ECs. Following LPS exposure, ECs proliferated, decreased EC markers CD31 and vascular endothelial Cadherin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…We previously reported that BPIFA2 binds LPS (Abdolhosseini et al, 2012) and affects the activity of ingested LPS and metabolic endotoxemia (Nandula et al, in press). In addition, renal stem/progenitor cells respond to an LPS insult by secretion of BPIFA2 (Sallustio et al, 2019). The results presented here expand the systemic effects to sodium intake and blood pressure control.…”
Section: Resultssupporting
confidence: 59%
“…We previously reported that BPIFA2 binds LPS (Abdolhosseini et al, 2012) and affects the activity of ingested LPS and metabolic endotoxemia (Nandula et al, in press). In addition, renal stem/progenitor cells respond to an LPS insult by secretion of BPIFA2 (Sallustio et al, 2019). The results presented here expand the systemic effects to sodium intake and blood pressure control.…”
Section: Resultssupporting
confidence: 59%
“…The cells are also introduced as a therapeutic option for kidney diseases due to the ability of multipotent differentiation, and reparative properties. They induce renewal of renal tissues, regenerating damaged cells, and repairing physical or chemical damage in the kidney [5][6][7]. However, the mechanism of renal stem cells in the repair of acute kidney impairment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Coculture with adult renal stem/progenitor cells (ARPCs) abrogates the LPS-induced EndMT process in a MyD88-independent manner. This effect could be due to the enhanced secretion of C-X-C motif chemokine 6 (CXCL6), serum amyloid A-4 protein (SAA4) and BPI fold-containing family A member 2 (BPIFA2) by ARPCs as has been proposed previously 43 .…”
Section: Discussionmentioning
confidence: 69%